Granulosa cell tumors of the ovary: A retrospective tertiary center experience - Bayramoğlu, Denizhan; Çintesun, Ersin; Şahin, Gözde; Karabağlı, Pınar; Bayramoğlu, Zeynep; Çelik, Çetin (Ortadoğu Reklam Tanıtım Yayıncılık Turizm Eğitim İnşaat Sanayi ve Ticaret A.Ş., 2021)
Objective: Granulosa cell tumor (GCT) of the ovary is an uncommon neoplasm with good prognosis. GCT is a rare ovarian malignancy originating from sex cord-stromal cells. The only clinically proven prognostic factor regarding recurrence is stage. In this study, we aimed to analyze the detailed clinical and histopathological prognostic parameters of this rare malignancy, based on the cases we experienced in our own clinic. Material and Methods: Forty-six patients who were followed up and treated with the diagnosis of granulosa cell ovarian tumor between 2010 and 2020 were evaluated retrospectively by scanning the patient archive files. Results: The median follow-up period was 52 months. The mean patient age was 55 years. The most common symptom was abdominal pain. The most common surgical procedure was total abdominal hysterectomy+bilateral salpingo-oophorectomy+pelvic/paraaortic lymph node dissection with 60.9% (n=28). Fertility sparing surgery was performed for 5 (10.9%) patients. In this study, a significant relationship was found between the survival and FIGO stage, nuclear atypia, mitotic rate. The rate of metastatic lymph nodes is very low in primary surgery and therefore may not be performed. Conclusion: GCT is one of the rare diseases of ovary. Since recurrence may occur even after many years, the follow-up period should be kept long. Stage is still the most important prognostic factor and is directly related to survival. In addition, the mitotic rate and nuclear atypia of the tumor may also be prognostic factors and have an impact on survival.
Keywords: Granulosa Cell Tumor; Ovary; Prognostic Factor; Sex Cord-Stromal Tumor